Socio-cultural conditioning of style and structure in journalistic discourse: The distinctively "objective" textuality of Iranian political news reporting. (March 2018) - Makki, Mohammad; White, Peter R.R.
Highlights: Socio-cultural conditioning of news reporting styles and genres in Iranian journalism. Highly "impersonalised" styles of Iranian political news reporting. Application of the appraisal framework to analyse journalistic discourse. Journalistic "objectivity" across cultures and languages. Abstract: There is virtually universal acceptance in the discourse-analysis literature that the stylistic and text-organisational properties of texts are conditioned by the social contexts in which they operate and the communicative purposes which they serve. This paper provides some new insights into this nexus between context and text via a report of a study into Iranian Farsi/Persian-language journalism – specifically into a particular type of political news reporting concerned with covering the speeches and announcements of high-status political figures. The paper provides evidence that these reports combine a distinctive generic structure with a distinctive writing style, "distinctive" at least in the sense that neither has hitherto been observed in the news reporting of other languages. With respect to generic structure, these reports do not operate with the so-called "inverted pyramid" structure, so often associated with English-language journalism, by which the opening headline/lead establishes a point or angle of maximal significance. With respect to their stylistic properties, these texts are highly constrained attitudinally, with even fewer instances of authorial assessment or interpretation than is typically the case in, for example, English-language "hard news" reporting. It is proposed that this apparently unique style-and-structure combination can plausibly be related to the unique cultural, political and religious conditions under which news journalism operates in Iran. It will be argued that this way of reporting political news reflects the subordination of news media organisations to the political establishment in that country.